Antimicrobial and anti-inflammatory activities of three halophyte plants from Algeria and detection of some biomolecules by HPLC-DAD. Issue 12 (31st May 2021) - Chekroun-Bechlaghem, Nadjat; Belyagoubi-Benhammou, Nabila; Belyagoubi, Larbi; Mansour, Sadia; Djebli, Noureddine; Bouakline, Houssam; Gismondi, Angelo; Nanni, Valentina; Di Marco, Gabriele; Canuti, Lorena; Canini, Antonella; Atik-Bekkara, Fouzia
Abstract: Antimicrobial activity of hydroalcoholic extracts (30/70) from leaves and stems of three halophytes ( Tamarix africana, Arthrocnemum macrostachyum and Suaeda fruticose ) was investigated. In vivo toxicological study and anti-inflammatory activity of leaf extract of T. africana were tested on carrageenan-induced inflammatory paw edema. T. africana possessed significant anti-inflammatory activity at 150 and 300 mg/kg confirmed by histological study of inflamed tissues. Six phenolic acids and 10 flavonoids where identified by HPLC–DAD. Gallic acid, Rutin and Kaempferol-3- O -glucoside were the major compounds. For the antibiotic assays, S. fruticosa leaf extract exhibited strong bactericidal power against S. aureus with MBC of 1.25 mg/mL whereas T. africana leaf and stem samples exhibited a significant bactericidal activity against S. aureus and B. subtilis compared to the negative control (Ampicillin and Chloramphenicol). Crude leaf and stem extracts from T. africana and stem extract from S. fruticosa exhibited a strong antifungal effect against C. albicans . Graphical Abstract: